SEED GERMINATION BIOLOGY OF RARE TULIPA SPECIES IN NORTHERN AND CENTRAL KAZAKHSTAN - Tagimanova , D.; Raiser , O.; Nagmetova, G.; Khapilina , O. (Eurasian Journal of Applied Biotechnology, 2025)
Kazakhstan has one of the highest diversities of Tulipa species, most of which are threatened. The threat of their extinction necessitates the use of biotechnological approaches, such as in vitro micropropagation, which allows the preservation of valuable genotypes without harming natural populations. In the process of increasing climate change and anthropogenic impact, these endemic species are at high risk of extinction. In this regard, the study and conservation of biodiversity of endemic plant species is considered a global priority throughout the world. The aim of the work was to study the effect of temperature and growth regulators on germination of T. auliekolica, T. turgaica seeds for their introduction into in vitro cultures. In vitro germination was carried out on ½ MS media with and without the addition of GA₃ (13 and 52 mg/l). Germination was recorded for 60 days, germination (%) and T₅₀ were calculated. According to the results of the tetrazolium test, the viability of T. turgaica and T. auliecolica seeds was 95% and 100%, respectively. The studied species showed different temperature preferences; for T. auliecolica seeds, the optimal temperature was 4°C, and for T. turgaica, 10°C. In addition, T. auliecolica seeds germinated faster than T. turgaica seeds. The results showed that temperature significantly affects seed germination. Seeds of both species germinated only at low temperatures (4 and 10°C), at 20°C, seed germination was absent in both species. The obtained data are of significant practical importance for the creation of effective methods for in vitro cultivation of these rare Tulipa species. Selection of optimal GA₃ concentrations in combination with temperature regimes significantly increases the success of in vitro propagation, which plays a key role in programs for the conservation of biodiversity of endemic plants.